Giant cell tumor of sellar region: A rare case report and review of literature (Journal of Pathology of Nepal, 2025)
Primary bone neoplasms are an uncommon group of neoplasms that include benign to malignant and locally aggressive or rarely metastasizing types. Giant cell tumor is a very rare tumor of the skull, with few of those reported cases arising from the sphenoid and temporal bone. Exact localisation is essential in the formulation of differential diagnosis between the diverse pathologies that affect this region. Herein, we discuss a case of Giant cell tumor in the sellar region.